P14.02 The Natural History of a Residual Intracranial Meningioma- Volumetric Growth and Predictors of Progression. (9th September 2021) - Gillespie, C S; Richardson, G E; Mustafa, M A; Islim, A I; Keshwara, S M; Taweel, B A; Bakhsh, A; Kumar, S; Millward, C P; Mehta, S; Rathi, N; Chavredakis, E; et al.
Abstract: BACKGROUND: Resection of meningioma leaves residual solid tumour in ~25% of patients. Selection for further treatment and follow-up strategy may benefit from knowledge of volumetric growth and associated prognostic factors. MATERIAL AND METHODS: Growth rates were assessed using a linear mixed effects model, in a retrospective adult cohort that underwent subtotal resection of meningioma (2004–2018). Endpoints were re-treatment, end of follow-up or death. Cox regression analysis was used to identify prognostic factors for progression, defined using the Response Assessment in Neuro-Oncology (RANO) volumetric criteria. RESULTS: 236 patients were included. Mean age at surgery was 56.3 years (SD=13.7) and 73.7% were female. WHO grades were 1 (n=195, 82.6%), 2 (n=40, 16.9%) and 3 (n=1, 0.5%). Adjuvant fractionated radiotherapy (fRT) was administered to 34 patients (14.4%), with no propensity towards higher WHO grade or residual volume. Median pre-operative meningioma and post-operative residual volumes were 34.0cm3 (IQR 16.0–63.0) and 2.0cm3 (IQR 0.8–5.2), respectively. Median follow-up was 64 months (IQR 42–104). Median absolute growth rate (AGR) and relative growth rate (RGR) were 0.1cm3/year and 4.3%/year, respectively. According to RANO criteria, 132 (55.9%) patients progressed, of which 13 (9.8%) developed symptoms. Median progression-free survival was 56 months (95% CI 43.1–69.0). Multivariable analysis identified adjuvant fRT (HR 1.7, [95% CI 1.0–2.8], P=0.046), skull base location (HR 1.5, [95% CI 1.0–2.4], P=0.047) and Ki-67 index (HR 3.7 [95% CI 1.3–10.8], P=0.017) as prognostic factors for volumetric progression. WHO grade was not significant (HR 1.0, [95% CI 0.5–1.7], P=0.905). Forty-nine patients who progressed (37.1%) underwent further treatment: fRT (n=19), re-operation (n=15), Stereotactic radiosurgery (SRS) (n=10) and surgery+adjuvant fRT (n=5). Of those, 8 (16.3%) progressed further (after re-operation [n=6] and SRS [n=2]). Seven were treated with a 2nd re-operation (n=3), fRT (n=3), and SRS (n=1). One patient progressed after a 2nd reoperation and was treated with SRS, after which they remained stable. Median survival was not reached. 5- and 10-year overall survival (OS) was 96% and 86% respectively. CONCLUSION: Growth rates of a residual meningioma vary with a dichotomy observed in progression rates. Half of patients with a residual meningioma showed radiological progression requiring multiple treatment to control the tumour. The other half demonstrate a more indolent course. Skull base location and higher Ki67 are important prognostic factors for progression and therefore, should be considered to stratify patients for adjuvant radiotherapy.